Triangular OverConorm with MCDM Methodology for Association Between Speaking Proficiency and Self-Assurance in English Language and Literature - Censhu Ouyang; Boqi Hou (Neutrosophic Sets and Systems)
A multifaceted assessment methodology for English language and literature courses in postsecondary educational institutions is presented in this study. The model incorporates qualitative and quantitative indicators across six fundamental criteria—Curriculum Design, Instructional Quality, Student Engagement, Research Output, Cultural Integration, and Language Proficiency Development—in recognition of the variety of educational techniques. These criteria are used to evaluate the efficacy of 18 options that reflect different departments, instructional approaches, or institutions. The multi-criteria decision-making (MCDM) methodology is used to deal with different criteria and alternatives. This study uses the COPRAS methodology to rank the alternatives. The triangular OverConorm is used in this study to deal with interval values of each criterion and alternatives. The sensitivity analysis is conducted to show the ranks of alternatives under different cases. We proposed six cases in weights criteria. The results contribute to the continuous improvement of the quality of humanities education by illuminating important program strengths and areas for improvement.